Do smaller labour market entry cohorts really reduce German unemployment? - Alfred Garloff; Carsten Pohl; Norbert Schanne (European Regional Science Association (ERSA), 2010)
In this paper we analyze the consequences of small labour-market entry cohorts on (un)employment in Western Germany. From a theoretical point of view, small entry cohorts may on the one hand reduce unemployment due to "inverse cohort crowding" or on the other hand increase unemployment if companies reduce jobs disproportionately. Empirically, several studies on cohort crowding for the USA also provide ambiguous evidence regarding the direction of the effect: labour markets may become tighter or less tight with the size of the entering cohort. The European labour market reaction on demographic changes is even less clear and the German case is especially interesting: Given the sharp decline in birth rates since the beginning of the 1970s and the relatively rigid labour market constitution, the German reaction is likely to differ from the US experience. In order to study the effect of cohort size on (un)employment, we use regional population data from the Federal Statistical Office of Germany and social security and unemployment data from the Federal Employment Agency and the IAB for the years 1978 to 2008. We account for the likely endogeneity of cohort size due to migration of the (young) workforce, using lagged birth rates as instruments. In addition, we allow for spatial autocorrelation across western German regions. Our results are good news for the (Western) German labour market: small entry cohorts are indeed likely to decrease the overall unemployment rate and thus to improve the situation of job-seekers, given the stability of the historical effect. Accordingly, the employment rate will, according to our results, increase.
Keywords: 330